Emphysematous Pyelonephritis with Renal Artery Pseudoaneurysm - Kevin Koo; Elias S. Hyams (Urology Case Reports, 2017)
Emphysematous pyelonephritis is an acute infection of the renal parenchyma and perinephric tissues caused by gas-forming microorganisms, resulting in the radiographic presence of gas in the kidney, collecting system, and surrounding spaces. Here we present a case of severe emphysematous pyelonephritis in the setting of Klebsiella urosepsis. Surgical exploration of the flank revealed infectious disintegration of the renal parenchyma into a large phlegmon. The post-operative course was complicated by renal artery pseudoaneurysm and cutaneous fistualization of a perinephric fluid collection. Despite the high rate of mortality associated with this condition, the patient survived and has remained clinically well.